Diaphragmatic endometriosis associated with pelvic endometriosis: a case report - Rafael Tito Marques de Matos; Maria Célia Mendes; Maíra Cristina Ribeiro Andrade; Carolina Gennari Verruma; Rui Alberto Ferriani; Rosana Maria dos Reis (BMC Women's Health)
Abstract Background Thoracic endometriosis is characterized by the presence of endometrial tissue in or around lungs and on the diaphragm and is frequently associated with pelvic endometriosis. Case presentation In this case report, a 22-year-old Caucasian patient reported right hypochondrium pain without other associated symptoms and was diagnosed with cholelithiasis. She underwent laparoscopic cholecystectomy, and an abdominal cavity examination revealed a diaphragmatic endometriotic nodule and endometriosis foci in the right diaphragm, pelvic ligaments, and left adnexal area. During the procedure, excision of the diaphragmatic endometriotic nodule and cauterization of the larger endometriosis foci in the diaphragm were also performed. After surgery, hormone therapy was administered as complementary treatment, which included a depot gonadotrophin-releasing hormone (GnRH) agonist for 5 months, followed by drospirenone 4 mg/day for 3 months. At the follow-up visit, the patient reported an improvement in right hypochondrium pain after surgery and complete remission after clinical treatment. Magnetic resonance imaging (MRI) performed before and after 6 months following the initiation of hormone therapy revealed a regression of diaphragmatic and pelvic endometriosis foci. Conclusion In our case, the combination of surgical treatment and hormone therapy was effective for managing pelvic and diaphragmatic endometriosis.